On-line identification of the chemical constituents of Polygoni Multiflori Radix by UHPLC-Q-ToF MS/MS - Wang, Xueting; Yang, Jianbo; Cheng, Xianlong; Wang, Ying; Gao, Huiyu; Song, Yunfei; Wei, Feng; Ma, Shuangcheng (Frontiers in Chemistry, 2023)
Introduction: Polygoni Multiflori Radix (PMR) is a type of Chinese herbal medicine with rich chemical composition and pharmacological activity used widely in medicine and food. However, in recent years, there have been increasing numbers of negative reports about its hepatotoxicity. Identification of its chemical constituents for quality control and safe use is very important. Methods: Three solvents of different polarities (water, 70% ethanol, and 95% ethanol solution) were used to extract the compounds from PMR. Extracts were analyzed and characterized by ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-ToF MS/MS) in the negative-ion mode. Results: 152 compounds were detected and identified: 50 anthraquinones, 33 stilbene derivatives, 21 flavonoids, seven naphthalene compounds, and 41 other compounds. Eight other compounds were reported for the first time in the PMR-related literature, and eight other compounds were potentially new compounds. Discussion: This study lays a solid foundation for the screening of toxicity and quality-control indicators of PMR.